2016
DOI: 10.1002/jssc.201600744
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative analysis of multiple components for quality control of Deng‐Zhan‐Sheng‐Mai capsules by ultra high performance liquid chromatography tandem mass spectrometry method coupled with chemometrics

Abstract: Deng-Zhan-Sheng-Mai capsules are a well-known traditional Chinese patent medicine that was developed in China for the treatment of ischemic stroke. Its quality control focuses on Erigerontis Herba but ignores the contributions of Ginseng Radix et Rhizoma, Schisandrae Chinensis Fructus, and Ophiopogonis Radix. To improve the quality standards for this medicine, this work reports the application of a systematic ultra high performance liquid chromatography tandem mass spectrometric method coupled with chemometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The product ion of m/z 285.0393 corresponded to the loss of GluA (176 Da), and the fragment ions at m/z 257.0398, 241.0446, and 267.0292 corresponded to [M–H–GluA–CO] – , [M–H–GluA–CO 2 ] – , and [M–H–GluA–H 2 O] – , respectively. The fragment ion at m/z 267.0292 further generated the product ions at m/z 239.0330 and 211.0414 by successive losses of CO. Next, the product ions at m/z 213.0573, 195.0473, and 167.0500 were produced by successive losses of CO, H 2 O and CO, respectively, from the fragment ion at m/z 241.0446 . Two groups of isomers with [M–H] – ions at m/z 477.0670 and 475.0878 including quercetin‐7‐ O ‐glucuronide ( 19 ), quercetin‐3‐ O ‐glucuronide ( 21 ) and galetin‐3‐ O ‐glucuronide ( 22 ), kaempferid‐7‐ O ‐glucuronide ( 33 ) and kaempferid‐3‐ O ‐glucuronide ( 35 ) were detected and tentatively identified according to their retention time and fragmentation patterns in the literature .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The product ion of m/z 285.0393 corresponded to the loss of GluA (176 Da), and the fragment ions at m/z 257.0398, 241.0446, and 267.0292 corresponded to [M–H–GluA–CO] – , [M–H–GluA–CO 2 ] – , and [M–H–GluA–H 2 O] – , respectively. The fragment ion at m/z 267.0292 further generated the product ions at m/z 239.0330 and 211.0414 by successive losses of CO. Next, the product ions at m/z 213.0573, 195.0473, and 167.0500 were produced by successive losses of CO, H 2 O and CO, respectively, from the fragment ion at m/z 241.0446 . Two groups of isomers with [M–H] – ions at m/z 477.0670 and 475.0878 including quercetin‐7‐ O ‐glucuronide ( 19 ), quercetin‐3‐ O ‐glucuronide ( 21 ) and galetin‐3‐ O ‐glucuronide ( 22 ), kaempferid‐7‐ O ‐glucuronide ( 33 ) and kaempferid‐3‐ O ‐glucuronide ( 35 ) were detected and tentatively identified according to their retention time and fragmentation patterns in the literature .…”
Section: Resultsmentioning
confidence: 99%
“…Compound 4 exhibited the [M–H] – ion at m/z 397.0770 and the fragmentation ion at m/z 235.0468 after losing a unit of caffeoyl, which indicated that it belongs to the COA group. Finally, 11 compounds ( 3 , 6 , 9 , 12 , 17 , 26 , 27 , 34 , 36 , 37 , and 39 ) belonging to the CQA group, seven compounds ( 11 , 14 , 15 , 28 , 29 , 32 , and 38 ) belonging to the CDOA group and five compounds ( 4 , 7 , 10 , 24 , and 25 ) belonging to the COA group were tentatively or unambiguously characterized based on the characteristic fragment ions, fragmentation patterns, and related literatures . In addition, the compounds 3 , 6 , 9 , 12 , 17 , 26 , 27 , 28 , and 34 were unambiguously identified by the reference standards.…”
Section: Resultsmentioning
confidence: 99%
“…It is useful to note the quality of herbs is the safeguard of the effectiveness and safety of herbs in traditional medicines [28][29][30][31]. Increasing public awareness and scientific interest has carried on research towards the establishment of the quality of traditional medicines research and quality standards, which as complex system engineering due to different methods and different opinions [32][33][34][35][36][37][38][39][40][41]. Quality marker (Q-marker), a new promise concept on QC, is chemical substances from herbal medicine and products such as tablet, decoction, and extract that are closely related to the functional properties of traditional medicines, which are inherent or formed in the process of preparation as markers of safety and effectiveness for QC.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical analysis is the basis to appreciate those multiple phytochemicals and metabolites of TCM formulas. Thus, a rapid and reliable method for comprehensive identification of the chemical constituents and metabolites is needed for the modernization of TCM formula .…”
Section: Introductionmentioning
confidence: 99%